Gamificación como apoyo a estudiantes de educación básica con Trastorno de Déficit de Atención. - Obando Illicachi, Gladys (2024)
The objective of this research work is to analyze the use of gamification as support for basic education students with Attention Deficit Disorders, whose approach used was quantitative framed in a field research of a descriptive nature, with a non-experimental design. The intentional sample represented by twenty-four teachers from the Nuestro Mundo Eco-Rio Educational Unit, in the city of Riobamba in the 2022-2023 school year, was used. The technique was the survey, using a structured questionnaire with 18 items, and dichotomous and polytomous response options, which was validated by the judgment of an expert in the area of Psychology. Among its main results is that 50% of the population surveyed use some gamification elements occasionally such as virtual rewards, leaderboards, levels, etc., to support students with ADD in teaching activities, there are difficulties in adapting the games to the individual needs of the students. From the documentary analysis and the results obtained, it is concluded that gamification is fundamental and positive to improve the academic performance of students with ADD.